2016
DOI: 10.4047/jap.2016.8.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Does the maxillary anterior ratio in Korean adults follow the Golden Proportion?

Abstract: PURPOSEThe purpose of this study was to determine the effect of changes in the horizontal plane angle on the mesiodistal width ratios of the maxillary anterior teeth during the acquisition of frontal view photographs, derive these ratios for Korean adults on the basis of the data obtained, and analyze them using the Golden Proportion as a reference.MATERIALS AND METHODSIn experiment I, 30 plaster casts were mounted on an articulator and positioned on the angle-measuring device with a center setting of 0°. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…In addition, it was first used for calculating the relationship of successive width of the anterior teeth and a corresponding smile (6,7). However, earlier studies have shown that the width of anterior natural teeth does not correspond to the golden proportion (8)(9)(10)(11)(12)(13)). Preston's proportion and RED were thus introduced as alternates for the golden proportion, despite the difference of their reported values (6,10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was first used for calculating the relationship of successive width of the anterior teeth and a corresponding smile (6,7). However, earlier studies have shown that the width of anterior natural teeth does not correspond to the golden proportion (8)(9)(10)(11)(12)(13)). Preston's proportion and RED were thus introduced as alternates for the golden proportion, despite the difference of their reported values (6,10).…”
Section: Introductionmentioning
confidence: 99%
“…The GP has been investigated and mentioned extensively in the dental literature (Levin, 1978, Preston, 1993, Qualtrough and Burke, 1994, Snow, 1999, Rosenstiel et al, 2000, Ward, 2001, Javaheri and Shahnavaz, 2002, Mahshid and Khoshvaghti, 2004, Simon, 2004, Hasanreisoglu et al, 2005, Ali Fayyad et al, 2006, Murthy and Ramani, 2008, Petricevic et al, 2008, Nikgoo et al, 2009, Chander et al, 2012, Pini et al, 2012, Meshramkar et al, 2013, Rossetti et al, 2013, Forster et al, 2013, Al-Marzok et al, 2013, Calçada et al, 2014, Sandeep et al, 2015, Jin et al, 2016, Bragatto et al, 2016, Kanaparthy et al, 2016, Koidou et al, 2018, Parciak et al, 2017, Al-Kaisy and Garib, 2017). It has been considered by many researchers as the most harmonious recurrent tooth-to-tooth ratio that occurs more consistently in aesthetically pleasing smiles (Richardson and Malhotra, 1975, Levin, 1978, Ward, 2001, Marquardt, 2002) and has long been proposed as an aesthetic guideline for restoring and replacing maxillary anterior teeth (Richer, 1971, Rosenstiel et al, 2001, Levin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Richetts5 reported that the golden ratio was useful for aesthetic restoration of the maxillary anterior teeth. However, previous reports have stated that the golden ratio was not readily observed in maxillary anterior teeth 67891011121314. In 1993, Preston6 reported that only 17% of maxillary anterior teeth met the golden ratio.…”
Section: Introductionmentioning
confidence: 97%